THE POSSIBILITY OF THE RIGHT TO RELIGION EMERGING AS A JUS COGENS NORM (PART 1) - David Abrahams; Tayla Dye (Obiter, 2016)
This article has been divided into two parts, owing to its nature and scope. The aim of the work is to explore the possibility of the right to religion emerging as a jus cogens norm. In Part One, the concept of jus cogens and its role in the international community, together with the nature of the right to religion, will be discussed. It is on this foundation that the reader will be able to understand why enforcement is such an issue when considering countries such as the Democratic People’s Republic of Korea, which serves as a case study and is discussed in detail in Part Two. Gross violations against the right to freedom of religion still exist despite the prevalence of international instruments protecting such rights. Something more needs to be done to hold human rights transgressors to account.